2011
DOI: 10.1016/j.cmet.2011.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Inositol Polyphosphate 4-Phosphatase B as a Regulator of Bone Mass in Mice and Humans

Abstract: Summary Osteoporosis is a multifactorial genetic disease characterized by reduction of bone mass due to dysregulation of osteoclast differentiation or maturation. Herein, we identified a novel regulator of osteoclastogenesis, the murine homologue of inositol polyphosphate 4-phosphatase type IIa (Inpp4bα). Expression of Inpp4bα is detected from early osteoclast differentiation to activation stage. Targeted expression of native Inpp4bα ex-vivo repressed whereas phosphatase-inactive Inpp4ba stimulated osteoclast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 38 publications
2
64
0
Order By: Relevance
“…This set includes TYROBP (5 DAP12), INPP4B, and OSTM1, which are important regulators of OC genesis in mouse and human hematopoiesis. [37][38][39] As other examples, we found that the transcription factors SPI1 (5 PU.1), GATA2, and LIMD1 were upregulated, in agreement with their proven role in mouse OC development. [40][41][42] Gfi-1, which contributes to DC development, 43 was downregulated.…”
Section: Discussionsupporting
confidence: 62%
“…This set includes TYROBP (5 DAP12), INPP4B, and OSTM1, which are important regulators of OC genesis in mouse and human hematopoiesis. [37][38][39] As other examples, we found that the transcription factors SPI1 (5 PU.1), GATA2, and LIMD1 were upregulated, in agreement with their proven role in mouse OC development. [40][41][42] Gfi-1, which contributes to DC development, 43 was downregulated.…”
Section: Discussionsupporting
confidence: 62%
“…A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 9 Interestingly, based on mouse models, INPP4 deficiency alone (potentially impacting PI(3,4)P2 accumulation), similar to SHIP deficiency (potentially impacting PIP3 accumulation), does not result in spontaneous tumor formation [38,49,50], while PTEN deficiency alone (potentially impacting accumulation of both lipids) has long been known to cause high incidence of cancer [51]. This raises the possibility that malignant transformation through PI3K dysregulation may require uncontrolled production of both PIP3 and PI(3,4)P2.…”
Section: Inpp4b In Cancermentioning
confidence: 96%
“…In vivo insights into the function of INPP4B were available using INPP4B deficient mice [38] with similar mutation to the weeble INPP4A deficient mice [29]. INPP4B deficiency did not lead A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 8 to major defects in development or life span but was associated with defects in bone homeostasis.…”
Section: Inpp4b Is a Modulator Of Osteoclast Differentiationmentioning
confidence: 98%
“…Culture medium was replaced every 2 days with fresh RANKL-containing complete medium. Cells were then fixed with formaldehyde (EMD Inc., Mississauga, ON, Canada) and processed for staining of tartrate-resistant acid phosphatase (TRAP), as described previously (27). Alternatively, they were stained with DAPI.…”
Section: Methodsmentioning
confidence: 99%